2017
DOI: 10.12965/jer.1734988.494
|View full text |Cite
|
Sign up to set email alerts
|

Low blood pressure is sustained during subsequent activities of daily living performed after power training in older women

Abstract: The present study aimed to examine the effects of a prior session of power training on blood pressure values during tasks that mimic the activities of daily living in hypertensive and normotensive older women. A randomized crossover experimental design was used for this study. Eleven older women (age, 66.1±1.2 years; body mass index, 26.7±4.8 kg/m2; systolic blood pressure, 133.9±23.4 mmHg) were recruited to participate. Volunteers were randomly underwent to a single session of physical exercise equalized by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It is well-accepted, that the chronic adaptations presented by the cardiovascular system in response to physical exercise may be due to the sum of the acute effects (Terra et al, 2008 ; Moreira et al, 2016 ). In this sense, an increasing number of studies have shown that a session of low-to-moderate load power exercise may cause post-exercise hypotension (PEH) in hypertensive older women (Coelho-Júnior et al, 2017a ; Coelho Junior et al, 2017b ). In addition, Arazi et al ( 2013 ) and Ramírez-Campillo et al ( 2016 ) demonstrated that PEH occurred independently of power exercise intensity (Arazi et al, 2013 ; Ramírez-Campillo et al, 2016 ), which is an important practical aspect for the prescription of exercise in hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-accepted, that the chronic adaptations presented by the cardiovascular system in response to physical exercise may be due to the sum of the acute effects (Terra et al, 2008 ; Moreira et al, 2016 ). In this sense, an increasing number of studies have shown that a session of low-to-moderate load power exercise may cause post-exercise hypotension (PEH) in hypertensive older women (Coelho-Júnior et al, 2017a ; Coelho Junior et al, 2017b ). In addition, Arazi et al ( 2013 ) and Ramírez-Campillo et al ( 2016 ) demonstrated that PEH occurred independently of power exercise intensity (Arazi et al, 2013 ; Ramírez-Campillo et al, 2016 ), which is an important practical aspect for the prescription of exercise in hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…All these features make power resistance exercise a secure and effective option to DUP programs. In fact, as the cardiovascular responses to power resistance exercise seem to be dependent on the velocity of concentric muscle contraction, regardless exercise intensity (Coelho-Júnior et al, 2017a ; Coelho Junior et al, 2017b ), it can be an excellent alternative to the lower exercise session of DUP. In addition, a lower cardiovascular stress may be expected during power resistance exercise performance, since it does not include high training loads, fatiguing exercises, and Valsalva maneuver, all variables associated with desirable increases on blood pressure during exercise (MacDougall et al, 1985 b).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings have practical applications, given that low BP levels after acute exercise may contribute to low cardiovascular risk during the performance of ADL [23,24]. Hence, health professionals responsible for exercise prescription in patients with RH should preferably prescribe COM exercise, instead of either AER or RES alone.…”
mentioning
confidence: 84%
“…PEH is found after aerobic (AER) and resistance (RES) exercises in NON-RH and normotensive people [19][20][21][22]. Furthermore, PEH may predict the success of exercise protocols [21,22] and likely contribute to low cardiovascular risk during the performance of activities of daily living [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…According to Cherup et al [35], increased aerobic capacity with PT may modify neural structures and stimulate vascular branching, contributing to improvements in neuronal function. This data suggest that the combination of these types of exercise training may elicit similar or greater changes in cognition than TRT alone, while older individuals are submitted to low cardiovascular and osteoarticular stresses [52][53][54]. However, no prior evidence investigated the effects of combined PT and TRT (PTRT) on cognitive function of older adults.…”
Section: Introductionmentioning
confidence: 96%